PENERAPAN METODE JUST IN TIME (JIT) UNTUK MENINGKATKAN EFISIENSI PERSEDIAAN BAHAN BAKU PADA HOME INDUSTRY “MULYA COLLECTION” JOMBANG - Rizka Rosita; Muhammad Hufron; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTApplication of Just In Time (JIT) Method to Improve Raw Material Inventoryat Home Industry “Mulya Collection” Jombang The purpose of this research is to find out whether the application of Just-In-Time method can improve the cost efficiency of raw material inventory in Home Industry Mulya Collection Jombang located on Jl. PB Sudirman, Denayar, Jombang Regency which is engaged in leather shoe craft. The analytical tool used in this study is descriptive qualitative analysis, where the authors do not use the elements of numbers, but done by explaining the descriptions and explanations, and methods used in this study is the method of data collection by way of documentation from the source. From the analysis result, it can be seen that the calculation result from the method used by the company is Rp 155,860,000 while the result from just in time is Rp 131,950,000 so the company can save raw material inventory cost Rp 23,910,000.Keywords: Just In Time, Supply, Cost efficiency and effectiveness.